PENERAPAN KEARIFAN LOKAL SYAIR MANOE PUCOK MELALUI PROJEK PENGUATAN PROFIL PELAJAR PANCASILA (P5) - Seriana -; Fitri Sri Wahyuningsih; Putri Khairani; Friska Ria Sitorus (Jurnal Bahasa Indonesia Prima (BIP), 2023)
This study aims to determine teachers' pedagogical competence in increasing students' motivation to learn Bahasa Indonesia. To find this out, the approach used in this research is qualitative, a description method with observational research instruments or observations and interviews with students and teachers. The research participants were Bahasa Indonesia teachers and several SMA Negeri 3 Medan students. The study found that some teachers understand the characteristics of students because there are still teachers who generalize learning and need to understand student learning styles. The teachers in SMA Negeri 3 Medan have been able to design lesson plans (RPP) with innovative learning models. Not all teachers carry out learning according to the lesson plan (RPP) previously designed. In addition, some educators have yet to be able to assess or evaluate learning authentically. All teachers play a role in developing students so that they can actualize the potential of students.